The problem of choosing between irreconcilable theoretical orientations: comment on Melchert (2016) - Joseph, Stephen (American Psychological Association, 2017)
Melchert (2016) argues that knowledge of psychological processes is now grounded in experimental tests of falsifiable theories that support a unified, paradigmatic understanding of human psychology. While his argument for leaving behind our preparadigmatic past of competing theoretical orientations is welcome, Melchert (2016) presents a perspective in which the degree to which this is currently possible is overstated. In this comment it is argued that scientific research does not replace paradigmatic assumptions but takes place within them. As such, it is not possible to take the theoretical orientations out of the practice of psychology, which is inevitably an expression of our philosophical assumptions of first principles.